Perancangan dan Pembuatan Website E-Commerce Mulia Kencana Motor - Ericko, Stefanus; Dewi, Lily Puspa; Rostianingsih, Silvia (Jurnal Infra, 2015)
Mulia Kencana Motor is a motorcycle repair shop. It sells spareparts which is located in Yogyakarta. Since it has opened until present, the selling-buying process is done directly, the user come to the seller, Mulia Kencana Motor, then buys the goods or either makes an order. Mulia Kencana Motor need to have an online website that could connect both parties to sell and buy via website, therefore the range area of customer will be expanded.Through website, Mulia Kencana Motor could do an online selling and expanding the selling area to bring more customers. It also makes more convenience to the buyer, they do not have to come to Mulia Kencana Motor to find the stock, but only by searching it on the website. Based on the result of the observatuin, website enables the customer to do goods tracking, online buying, checking the shipping cost by JNE service. With the results of a questionnaire conducted by 76,5 % getting results we can conclude that it is feasible to use the website Kencana Mulia Motor